A Case of Tuberculous Meningitis With Concomitant Spinal Co-infection With Tuberculosis and - Candice A. Sternberg MD; Andres Martinez DO; Ayoola Olayiwola MD; Maria Morel Almonte MD; Christine A. Vu PharmD; Tanya Quiroz MSN; Nadine Montreuil MD; Folusakin Ayoade MD (Journal of Investigative Medicine High Impact Case Reports)
Co-infection with Mycobacterium tuberculosis and Aspergillus in an immunocompetent host is rare but can occur. In this case, we present a patient with central nervous system tuberculosis (TB) and biopsy-proven spinal co-infections with TB and Aspergillosis. We highlight the complexities of treating a TB-Aspergillosis co-infection given drug-drug interactions between standard therapy for both conditions. Using susceptibilities for the Aspergillus and carefully monitoring drug levels of the antifungal agents, we were able to optimally treat the co-infection. This patient was ultimately discharged on isoniazid 1200 mg (15 mg/kg) daily, levofloxacin 750 mg daily, rifabutin 450 mg daily, and posaconazole 300 mg twice daily with a tentative plan to treat for at least 1 year with close outpatient follow-up. This case can serve as a guide for other providers who need to treat cases of TB and Aspergillosis co-infection by learning from our experience and paying attention to potential pitfalls.